Pendidikan Karakter Kewirausahaan di Sekolah Menegah Kejuruan untuk Meningkatkan Minat Berwirausaha di SMK Negeri 1 Sakra - Hermany Hermany (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2019)
The superiority of the Vocational High School compared to other middle schools is that the students are trained to become entrepreneurs. The education model that is always developed in vocational schools to conduct entrepreneurship education is a model of entrepreneurship character education. The purpose of this study was to obtain an appropriate educational model for implementing entrepreneurship character education in SMKs to explore the experience of SMK students in implementing Character models in entrepreneurship learning. The focus of research on how students internalize character values, aspects of soft skills and transferable skills in learning Entrepreneurship so that students are interested in entrepreneurship, the research approach is qualitative phenomenological. A research orientation to understand, explore, and interpret the meaning of events, phenomena and relationships with people naturally in certain situations, during the entrepreneurial learning process. Data collected through observation, interviews and documentation are described as is. Opinions of students, educators, behavior, attitudes, interests, skills, weaknesses, are an important part of providing input to the improvement of entrepreneurial learning. The findings show that the enthusiasm of students is high, indicated by activities in five stages, the entrepreneurship project starts from (1) Small groups, (2) Exploration, (3) Development of business ideas, (4) Preparation and Presentation of business plans, ( 5) Action and business competition, running smoothly and successfully internalizing 3 character values and 5 soft skills-transferable skills with a high score of 68% and a moderate score of 32%. All products are sold out and some products have received orders, this shows an indication of growing entrepreneurial interest.